Inhibition of enzymatic activities of Bothrops asper snake venom and docking analysis of compounds from plants used in Central America to treat snakebite envenoming - Saravia Otten, Patricia (2022)
Ethnopharmacological relevance Snakebite envenoming is a public health problem of high impact in Central America. Bothrops asper, known as barba amarilla, terciopelo, and equis, is the snake species responsible for most snakebites in Central America. In this region, there is a long-standing tradition on the use of plants in the management of snakebites, especially in indigenous communities. Ethnomedical use of Eryngium foetidum L., Neurolaena lobata (L.) Cass. and Pimenta dioica (L.) Merr. to treat snakebite envenoming has been reported in Belice, Guatemala, Nicaragua, and Costa Rica. Extracts of the leaves of these plants have shown anti-venom activities in in vitro assays in previous studies. Aim of the study To assess the ability of organic fractions from these three plants to inhibit enzymatic activities associated with toxicity of the venom of B. asper, and to study, by docking analysis, the interaction of metalloproteinase and phospholipases A2 (PLA2) from B. asper venom with secondary metabolites previously described in these plants. Materials and methods Organic fractions were obtained from these three plant species and their ability to neutralize proteolytic, PLA2 and in vitro coagulant activities of B. asper venom was assessed. A phytochemical analysis was carried out in these fractions. The interaction of secondary metabolites previously described in these plants with three toxins from B. asper venom (a metalloproteinase, a PLA2 and a PLA2 homologue) was investigated by docking analysis. Results The inhibitory activity of plants was mainly concentrated in their polar fractions. Acetonic fraction from P. dioica was the most active against PLA2 activity, while the acetonic fraction of E. foetidum completely inhibited the proteolytic activity of the venom. Coagulant activity was partially inhibited only by the acetone and ethyl acetate fractions of P. dioica. Phytochemical analysis of the most bioactive fractions identified flavonoids, saponins, essential oils, coumarins, alkaloids, tannins and sesquiterpene lactones. Docking analysis revealed high affinity interactions of several secondary metabolites of these plants with residues in the vicinity of the catalytic site of these enzymes and, in the case of PLA2 homologue myotoxin II, in the hydrophobic channel. Conclusions Various fractions from these plants have inhibitory activity against enzymatic actions of B. asper venom which are directly associated with toxicological effects. Docking analysis showed structural evidence of the interaction of secondary metabolites with three toxins. These observations provide support to the potential of these plants to inhibit relevant toxic components of this snake venom.